Effect of Tele-exercise Interventions on Quality of Life in Cancer Patients: A Meta-analysis - Xiaoli Chen; Chuanmei Zhu; Juejin Li; Lin Zhou; Shu Zhang; Yun Zhang; Xiaolin Hu (Elsevier, 2024)
Summary: Purpose: To evaluate the impacts of tele-exercise intervention with cancer patients' quality of life, taking into account the influence of the duration of tele-exercise intervention, type of intervention, and gender of cancer patients on quality of life. Methods: The PubMed (MEDLINE), Embase, CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, and PsycINFO databases were searched from inception to August 21, 2023. The Cochrane Collaboration's risk of bias tool 2 was utilized to estimate the risk of bias, and the Grading of Recommendations, Assessment. For statistical analyses, R Studio was employed. Results: This meta-analysis contained eight trials. When compared to controls, tele-exercise interventions (SMD = 0.41, 95% CI: 0.12 to 0.70, p < .010; I2 = 54%, p = .030) have a positive influence on boosting the quality of life within cancer patients. Subgroup analyses demonstrated the greater effectiveness of tele-exercise in enhancing the quality of life of cancer patients when the duration was greater than or equal to 10 weeks. Furthermore, tele-exercise was found to have a stronger advantageous effect on quality of life among female cancer. In addition, among the types of interventions for tele-exercise, neither web-based nor telephone-based formats significantly enhanced quality of life among cancer patients. Conclusion: Tele-exercise interventions are a cost-effective and feasible non-pharmacologic complementary way to promote cancer patients' quality of life. Additional large-sample, carefully designed randomized controlled trials are warranted to further validate the impact of tele-exercise concerning cancer patients' quality of life. Registration number: CRD42023477147.